Enseñanza de la Química Sostenible en las carreras de ingeniería - Soledad Rodríguez, Beatriz Elena (2018)
Green Chemistry was born in 1990 in order to prevent environmental pollution, improve the environment and quality of life. It seeks to create awareness in both the scientific and industrial communities, the importance of providing goods and services that are in line with population growth, in a way that does not contaminate or diminish social welfare. Sustainable engineering has developed as an extension to sustainable chemistry,with the aim of designing products and processes that minimize pollution and companies that want to be recognized as leaders in a more global and competitive market must seek to bring value to their investments and the socio-economic environment in which they operate, with a high level of environmental protection.